Global burden and socioeconomic impact of knee osteoarthritis: a comprehensive analysis - Li, Erliang; Tan, Jianshi; Xu, Ke; Pan, Ying; Xu, Peng (Frontiers in Medicine, 2024)
To report the trend changes of the prevalence, incidence, and disability-adjusted life years (DALYs) of knee osteoarthritis (KOA) according to age, sex, sociodemographic index (SDI), and income. Methods This analysis used estimates from the broader Global Burden of Disease (GBD) study 2019, which covered 201 countries from 1990 to 2019. National prevalence, incidence, and DALYs were shown by using ggplot2 and maps packages. Five-year intervals were used for age groupings. The Commonwealth and the World Bank income classifications were used for income grouping.Globally, there were approximately 364.58 million prevalent cases (females: 225.16 million), 29.51 million incident cases (females: 17.53 million), and 11.53 million DALYs (females: 7.09 million) due to KOA in 2019. The Western Pacific Region had a high endemicity of approximately 7319.87 cases per 100,000 people (7.64%). Japan's prevalence rate (12610.12 cases per 100,000 population) was 10 times that of Somalia (1178.23) in 2019. In 200 countries (except the United Arab Emirates), the prevalence, incidence, and DALY rates of KOA in 2019 were higher among females than among males and increased with age up to the oldest age group. the prevalence was highest in the high-middle SDI countries, and the incidence and DALYs were highest in the middle SDI countries.There was a large burden of KOA worldwide, with some notable intercountry variation. Some countries had 10 times the burden of other countries. Increasing population awareness regarding the prevalence, incidence, and DALYs of KOA with a focus on the population in the Western Pacific Region is needed, particularly for older females. informs health policy development, and contributes to improving the efficiency, equity, and effectiveness of healthcare systems.